Landscape heritage and sustainable tourism in the post-COVID period - Uptake article - D'Orazio A.; Prezioso M. (ESPON, 2021)
On the 25th of February 2021 the ESPON-TNO program organised a virtual Peer Learning Workshop with ESPON researchers and academic and Icelandic stakeholders. The goal of the event was to nurture the ongoing discussion in Iceland about developing a new tourism strategy based on national landscape and cultural heritage, providing examples of territorial-specific approaches to facing developmental challenges. The main goal of the event was to develop a better understanding of which policies and local practices can relaunch tourism in a sustainable manner, adapted to the context of the global pandemic without having a negative impact on the country’s heritage. This transition period provides an opportunity to rethink the role of tourism in Iceland’s future policy-strategies. In this context, the knowledge from ESPON could inspire national and regional stakeholders in elaborating policy and planning instruments building on trans-European knowledge and case studies from other countries.